Repeat infection with gonorrhoea in Sheffield, UK: predictable and preventable?. Issue 1 (20th June 2012) - Hughes, Gwenda; Nichols, Tom; Peters, Lindsey; Bell, Gill; Leong, Geraldine; Kinghorn, George
Abstract : Background: Repeat infection with gonorrhoea may contribute significantly to infection persistence and health service workload. The authors investigated whether repeat infection is associated with particular subgroups who may benefit from tailored interventions. Methods: Data on gonorrhoea diagnoses between 2004 and 2008 were obtained from Sheffield sexually transmitted infection clinic. Kaplan–Meier survival curves were used to estimate the percentage of patients with repeat diagnoses within a year, and a Cox proportional hazard model was used to investigate associated risk factors. Results: Of 1650 patients diagnosed with gonorrhoea, 7.7% (95% CI 6.5% to 9.1%) had a repeat diagnosis within 1 year. Men who have sex with men under 30, teenage heterosexuals, black Caribbeans, people living in deprived areas and those diagnosed in 2004 were most likely to re-present. Of those patients (53%) providing additional behavioural data, repeat diagnosis was more common in those reporting prior history of gonorrhoea, any previous sexually transmitted infection diagnoses, two or more partners in the past 3 months and a high-risk partner in the past year. In an adjusted analysis, repeat diagnosis was independently associated with being a young man who has sex with men, living in a deprived area, a history of gonorrhoea and being diagnosed in 2004 but was most strongly associated with non-completion of behavioural data forms. Conclusions: Groups most at risk of repeat infection with gonorrhoea are highly predictable but are disinclined to provide detailed information on their sexual behaviour. Care pathways including targeted and intensive one-to-one risk reduction counselling, effective partner notification and offers of re-testing could deliver considerable public health benefit.